2020
DOI: 10.1016/j.coelec.2020.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Architected porous metals in electrochemical energy storage

Abstract: Porous metallic structures are regularly used in electrochemical energy storage devices as supports, current collectors or active electrode materials. Bulk metal porosification, dealloying, welding or chemical synthesis routes involving crystal growth or self-assembly for example, can sometimes provide limited control of porous length scale, ordering, periodicity, reproducibility, porosity and surface area. Additive manufacturing and 3D printing has shown the potential to revolutionize the fabrication of archi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…Here, mass transport can be correlated and controlled to the pressure drop and flow dispersion to evaluate the overall cost-benefit of the electrodes. The significance of 3D and porous architecture can be realized when structures such as nanorods, nanospheres, nano-onions, networks of nanowires and nanoflowers, micro-flowers, nano walls, etc., are manufactured on flat plate electrodes or inside already three-dimensional electrodes ( Egorov and O'Dwyer, 2020 ). The electrochemical properties can be tailored by surface treatment or deposition of electrocatalysts.…”
Section: Electrode Design In Electrocatalytic Reaction Involving Wate...mentioning
confidence: 99%
“…Here, mass transport can be correlated and controlled to the pressure drop and flow dispersion to evaluate the overall cost-benefit of the electrodes. The significance of 3D and porous architecture can be realized when structures such as nanorods, nanospheres, nano-onions, networks of nanowires and nanoflowers, micro-flowers, nano walls, etc., are manufactured on flat plate electrodes or inside already three-dimensional electrodes ( Egorov and O'Dwyer, 2020 ). The electrochemical properties can be tailored by surface treatment or deposition of electrocatalysts.…”
Section: Electrode Design In Electrocatalytic Reaction Involving Wate...mentioning
confidence: 99%
“…143 However recent rigorous works using a variety of meso-/macroporous metallic electrodes have shown that meso-/macoroporosity can control the electrode process. 40,77,144,145 Furthermore, a confinement environment is shown as an alternative approach to control (electro)catalytic reactions. 40,146 MOFs/COFs are recently used as buildingblocks to construct novel-type heterojunction electrocatalysts, which interestingly suggested not only to improve activities but also selectivity at the same time by taking advantage of molecular-level structural designability.…”
Section: Future Vision On Mofs/cofs As Model Electrochemical Systemsmentioning
confidence: 99%
“…40,146 MOFs/COFs are recently used as buildingblocks to construct novel-type heterojunction electrocatalysts, which interestingly suggested not only to improve activities but also selectivity at the same time by taking advantage of molecular-level structural designability. [147][148][149][150] Considering that the meso-/macroporosity of the metallic electrodes plays a pivotal role in control of the electrode process, 40,77,144,145 designing hierarchical constructions of the electrodes with MOFs/COFs as building-blocks can provide further control of the electrode process including the activity and the selectivity.…”
Section: Future Vision On Mofs/cofs As Model Electrochemical Systemsmentioning
confidence: 99%
“…Remarkably, the mass loadings of electrodes prepared by the conventional slurry-pasting method are generally less than 2.0 mg cm –2 , far lower than the industry requirement (∼10 mg cm –2 ). Moreover, polymer binders, conductive additives, and solvents inevitably reduce the overall capacitance and increase production costs. In this context, the in situ growth of active materials directly on the 3D conductive matrix, for example, Ni foams, due to high conductivity, strong alkali resistance, uniform pore structure, and good mechanical strength, are emerging as an alternative fabrication technology and attracting extensive attention. The obtained self-standing electrodes can avoid using additional inactive materials and the complicated preparation procedures and enable the tight binding of active materials on the current collector with the concurrent prevention of material agglomeration. However, traditional Ni foams are facing some bottlenecks in this scenario, which can be exemplified by its intrinsically small SSA that severely limits the mass loading capability (generally 0.8–5.0 mg cm –2 ). To the best of our knowledge, the previously reported highest mass loading of the in situ grown active materials on the Ni foam was ∼18 mg cm –2 , showing an area-specific capacitance of 2.79 F cm –2 .…”
Section: Introductionmentioning
confidence: 99%